Uncertainty budget for sup226Ra activity concentration in water by alpha spectrometry - Spasova, Yana (Acta chimica slovenica, 2007)
Alpha-particle spectrometry is the most frequently used technique for the activity determination of alpha emitters, such as radium, uranium, plutonium, americium and thorium in environmental samples. In this paper an extensive uncertainty budget is presented for a typical aplpha particle spectrometry measurement of the sup226Ra activity concentration in drinking water. The most influental parameters contributing to the uncertainty are investigated. The set-up used is a common aplha-spectrometry system for environmental samples using PIPS detectors. In particular, the influence of geometrical parameters as well as the activity distribution in the measured sources on thesolid angle is scrutinised.
Keywords: analizna kemija; kemija okolja; merilna negotovost; pitna voda; radon; spektrometrija